2009
DOI: 10.1111/j.1439-0426.2009.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

Life-history variations of killifish (Aphanius sophiae) populations in two environmentally different habitats in central Iran

Abstract: Two populations of Aphanius sophiae from two different habitats (one in a spring with stable environmental conditions and the other in a river with variable conditions) were examined to determine whether these conditions elicit differences in life history traits. Age composition revealed that females from the spring live longer. Von Bertalanffy growth parameters showed that L(¥) in the river population was higher than in the spring population. GSI showed a shorter reproduction period in A. sophiae from the riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
6
13
0
Order By: Relevance
“…The size of the oil droplets may change in individuals based on genetics and age of the embryo (Cunningham & Balon, ). These results confirm the hypothesis of the response of killifish to local selective pressures in different habitats through adaptations via changes in the duration of the reproductive period and egg diameter (Kamal et al., ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The size of the oil droplets may change in individuals based on genetics and age of the embryo (Cunningham & Balon, ). These results confirm the hypothesis of the response of killifish to local selective pressures in different habitats through adaptations via changes in the duration of the reproductive period and egg diameter (Kamal et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…Based on the data of Kamal, Bakhtiyari, Abdoli, Eagderi, and Karami (), average diameter of mature eggs of A. sophiae from Shour River (Namak Lake basin) was 1.401 ± 0.19 mm with minimum and maximum diameters of 0.66 and 2.23 respectively. According to Sezen and Olmez () the eggs of A. mento are spherical, transparent and sticky, and full of egg yolks with 7–8 oil droplets, having adhesion filaments on the surface with average diameter of 1.589 ± 0.50 mm.…”
Section: Discussionmentioning
confidence: 99%
“…For A. fasciatus from Mesolongi and Etolikon lagoons, the values were calculated as 94.44 mm and 79.22 mm for females and males, respectively (Leonardos and Sinis, 1999). Seasonal change in GSI values indicates an extended spawning period; this strategy has also been found in many other studies (Ferna´ndez-Delgado et al, 1988;Garcia-Berthou and Moreno-Ami, 1992;Leonardos and Sinis, 1998;Keivany and Soofiany, 2004;Kamal et al, 2009;Gu¨c¸lu¨and Ku¨c¸u¨k, 2011). It has been stated that L ∞ increased in length with the decline of the temperature (Basilone et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…They were commonly identified as Aphanius sophiae (Heckel, 1849) (Coad and Abdoli 2000; Kamal et al 2009); however, it was shown that the true Aphanius sophiae is restricted to the endorheic Kor River basin near Shiraz (Fars Province) (Coad 2009; Esmaeili et al 2012). This study describes a newly discovered Aphanius population from the Namak Lake basin in northern central Iran (Fig.…”
Section: Introductionmentioning
confidence: 99%